CULTURE AS THE MENTAL SPACE OF CIVILIZATION - Моkliak, Larisa (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. In modern humanitarian thought, the thesis is traced and supported that the fundamental values of history are being formed rather by invariants of historical activity, having preserved in the body and spirit of culture than changes in the socio-economic progress. The aim and tasks of the study are to analyze the connection between the civilizational processes of the modern global world and culture, their interdependence, specific features inherent in modern civilization and culture, trends, ways, and place of culture in the process of overcoming the anthropological crisis of modernity; to reveal the role of intercultural dialogue in the system of modern civilizational processes. The theoretical basis of the study was the work of Ukrainian and foreign researchers devoted to the problems of culture and civilization in the field of philosophy of culture, cultural studies, sociology, and psychology. Dialectical, systemic, interdisciplinary, and comparative research methods were used. Research results. As a result of clarifying the content of the concepts of "civilization", "culture", and "mentality", the dichotomy "civilization - culture" is considered in the study as two dialectically conditioned sides of the socio-historical process. One of them ‒ civilization ‒ represents the social organization of the social life of individuals, the integrity of their world based on the reproduction of social wealth, which allows and ensures their existence and development. The other side, culture, represents the existential experience inherent in civilization, invariant structures, and enduring universal human values. Discussion. Culture, on the one hand, is determined by the needs of the social practice of a particular stage in the development of civilization, which is expressed in the form of public interests, and on the other hand, culture is characterized by relative independence, internal sources of self-development and functioning mechanisms. Conclusion. As a result of understanding and discussing the topic, the author comes to the conclusion that culture provides a semantic field for the interaction of different spheres of activity, when knowledge, norms, methods, techniques, rules, and values from one form of culture pass into others, are rethought there and stimulate the development of their content. Culture creates the semantic space of civilization, its "force field", which can be called mental.